ASPEK PRAGMATIK DALAM IKLAN AXIS PADA MEDIA AUDIO VISUAL - Suaibah Suparman, Neneng Siti; Setiawan, Ridwan; Nugraha, Via (IKIP Siliwangi, 2018)
This study attempts to describe the pragmatic aspects contained in Axis advertising. The method used in this study used a qualitative approach with descriptive-analysis method. The purpose of this study to determine the meaning contained in Axis advertising in terms of pragmatic. The result of this research is the use of language in Axis advertisement get 4 kinds in a pragmatic aspect that is, direct speech act, an act of directive speech, an act of speech illocution, and not representative speech. In addition, the use of language in axis ads is only to attract viewers to buy their products and means that in axis ads very sparingly if used for browsing like video calls, streaming video, and upload photos.